PENDAMPINGAN PEMASARAN PRODUK MENGGUNAKAN INSTAGRAM BAGI PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) DI KECAMATAN PATHUK GUNUNG KIDUL - Sudaryanto, .; Sajati, Haruno; Kusumaningrum, Anggraini; Nugraheny, Dwi; Aryanto, Salam; Wintolo, Hero (Sekolah Tinggi Teknologi Adisutjipto, 2020)
Micro, Small, Medium Enterprises (MSME) products in the Pathuk District of Gunung Kidul Regency covering of food, crafts and tourism. The SMEs living in the villages of Pathuk, Salam, Ngoro ngoro, Terbah, Nglanggeran, Semoyo, Pengkok, Putat, Bunder, and Nglegi attended training held at the Office of the Village Cooperation Agency (BKN) Pathuk District. Some participants have products that already have a Food License for Home Industry. The market asistance using Instagram for social media material involved alumni and students from the Adisutjipto College of Information Technology Department. The results in the form of marketing and promotion using Instagram with the hashtag #pkmdepartemeninformatikastta with good criteria results of 27.8%, enough by 61.1% and less good by 11.1%